2020
DOI: 10.1002/cam4.3141
|View full text |Cite
|
Sign up to set email alerts
|

MASTL: A novel therapeutic target for Cancer Malignancy

Abstract: Targeting mitotic kinases is an emerging anticancer approach with promising preclinical outcomes. Microtubule‐associated serine/threonine kinase like (MASTL), also known as Greatwall (Gwl), is an important mitotic kinase that regulates mitotic progression of normal or transformed cells by blocking the activity of tumor suppressor protein phosphatase 2A (PP2A). MASTL upregulation has now been detected in multiple cancer types and associated with aggressive clinicopathological features. Apart, an aberrant MASTL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…The kinase MAP3K2 (MEKK2) activates the MEK5/ERK5 cell signaling pathway and is thought to play an important role in tumor growth and metastasis 1 . MASTL, or microtubule-associated serine/threonine kinase like, is an important mitotic kinase that regulates mitotic progression of normal or transformed cells by blocking tumor suppressor protein phosphatase 2A (PP2A) activity, where MASTL deregulation has been detected in multiple cancer types and associated with aggressive clinicopathological features 24 . The spindle assembly checkpoint kinase TTK (Mps1) is a key regulator of chromosome segregation, with functional roles demonstrated for multiple cancer types 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinase MAP3K2 (MEKK2) activates the MEK5/ERK5 cell signaling pathway and is thought to play an important role in tumor growth and metastasis 1 . MASTL, or microtubule-associated serine/threonine kinase like, is an important mitotic kinase that regulates mitotic progression of normal or transformed cells by blocking tumor suppressor protein phosphatase 2A (PP2A) activity, where MASTL deregulation has been detected in multiple cancer types and associated with aggressive clinicopathological features 24 . The spindle assembly checkpoint kinase TTK (Mps1) is a key regulator of chromosome segregation, with functional roles demonstrated for multiple cancer types 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The spindle assembly checkpoint kinase TTK (Mps1) is a key regulator of chromosome segregation, with functional roles demonstrated for multiple cancer types 28 . Inhibitors exist for MAP3K2, MASTL, and TTK 1 , 24 , 28 . Previously studied in other cancer types, these kinases may represent therapeutic targets for uterine endometrial cancer in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies suggest that MASTL is a promising target for selective anticancer treatment [ 16 ], MASTL inhibitors with nM range potency and antitumor efficacy have not been reported. Our previous report showed that MKI-1 was an MASTL inhibitor with antitumor activities in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that MASTL acts as an oncogenic kinase by inactivating tumor suppressive PP2A-B55 complex in breast cancer cells [11][12][13], thereby regulating various oncogenic properties, such as cellular transformation, chromosome instability, and Pharmaceuticals 2021, 14, 647. https://doi.org/10.3390/ph14070647 https://www.mdpi.com/journal/pharmaceuticals Pharmaceuticals 2021, 14, 647 2 of 12 metastasis [3,14,15]. MASTL targeting has reduced tumor growth in various in vitro and in vivo tumor models [13,16]. Notably, MASTL are highly expressed in multiple types of cancers, including breast, head and neck, gastric, thyroid, and colorectal cancers [12,15,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to wild type mice, GSK3β expression is significantly reduced in the prostate epithelial cells of RKIP −/− mice [ 81 ], supporting the regulation being physiologically relevant. GSK3β possesses tumor suppressing function via inhibiting the Wnt/β-catenin pathway [ 83 ], EMT, and cyclin D1 expression [ 81 ].…”
Section: The Molecular Basis For Rkip As a Tumor Suppressormentioning
confidence: 99%